Different Legal Origins, Equal Evidentiary Force: A Comparative Study of Redistribution and Sale-Based Land Certificates in Indonesia - Nurbaedah Nurbaedah (Yustisia, 2026)
In the unified land registration system of Indonesia, the land title certificates are the primary evidence of ownership. Certificates issued through land redistribution and private sale have the same legal validity under the same registration framework, but their different legal origins present unsolved concerns of legal certainty, property rights, and agrarian justice. There is a large number of literature on land redistribution, land markets, and tenure security in Vietnam, China, and the Philippines, but little study on how different acquisition mechanisms affect the evidentiary character of land certificates in a single registration system. This study aims to fill such a gap by legal research using statutory, conceptual, and comparative methods. The results reveals that redistribution and sale-based certificates have the same evidentiary strength as strong but rebuttable proof of ownership under Indonesian land law. But they vary considerably in terms of legal origin, transferability, administrative constraints, and policy purposes. The market-oriented certificates are meant to expedite the process of property sales, while the redistribution certificates have temporary transfer restrictions to maintain the aims of agrarian reform. The findings position Indonesia within the global debate on balancing market efficiency and social justice in land governance. This study claims that Indonesia's unified land registration system demonstrates how certificates with equal legal validity can embody different property rights while promoting legal certainty, equitable land distribution, and sustainable land governance